Social capital, knowledge sharing, work meaningfulness and creativity: evidence from the Pakistani pharmaceutical industry - Bhatti, S. H.; Vorobyev, D.; Zakariya, R.; Christofi, Michael (My University, 2021)
Purpose: As an integral part of intellectual capital (IC), social capital (SC) has been studied as an asset crucial to social relationships among individuals and groups of individuals, which in turn have a significant impact on organizational performance outcomes. This study investigates the impact of organizational social capital (OSC) on employee creativity through the mediation role of knowledge sharing (KS) and moderation of work meaningfulness (WM). Design/methodology/approach: The authors base the analysis on employee-level data gathered via a cross-sectional survey designed for this study. The authors surveyed 217 employees of the pharmaceutical industry in Pakistan. The authors run a confirmatory factor analysis (CFA) and use structural equation modeling (SEM) and Hayes method to test the hypotheses. Findings: The authors find that OSC positively affects employees’ willingness to share their knowledge with colleagues, which in turn has a positive effect on employee creativity (EC). The results also show that the relationship between social capital and knowledge sharing is moderated by work meaningfulness. Research limitations/implications: This study contributes to the IC in general and the SC literature in particular, by providing empirical evidence that shows how creativity could be a focal and pivotal performance outcome of organizational social capital through the moderated mediation roles of work meaningfulness and knowledge sharing. Originality/value: The authors adopt the concept of SC from the organizational level to the individual level, examining how an individual's perception of organizational capital influences his or her creative behavior and exploring the role of KS and job meaningfulness (JM) in this relationship.
Keywords: Social capital; Employee creativity; Knowledge sharing; Work meaningfulness